Peripheral or Marginal Participation? University-Based Intensive English Programs as an Entryway to U.S. Academia - Grosik, Sarah; Kanno, Yasuko (Journal of International Students, 2021)
For academically bound international students, university-based Intensive English Programs (IEPs) frequently function as an avenue to American undergraduate or graduate degree programs. This qualitative study examined how one university-based IEP was preparing its academically bound international students and facilitating their transitions to matriculated study. Lave and Wenger’s (1991) theory of Situated Learning was utilized to explore international students’ participation in the IEP as a community of practice and the IEP’s own marginality within the university structure. We found that university-based IEPs can play a critical role in helping international students gain the competence and knowledge necessary to begin legitimate peripheral participation in degree programs. However, the extent to which IEP students were able to participate in the larger university community was limited by the IEP’s own marginality in the university community and the fact that the IEP is ultimately not a discipline-specific community of practice.